Cooling Intensification of a Continuously Moving Stretching Surface Using Different Types of Nanofluids - M. B. Akgül; M. Pakdemirli (Journal of Applied Mathematics)
The effect of different types of nanoparticles on the heat transfer from a continuously moving stretching surface in a concurrent, parallel free stream has been studied. The stretching surface is assumed to have power-law velocity and temperature. The governing equations are converted into a dimensionless system of equations using nonsimilarity variables. Resulting equations are solved numerically for various values of flow parameters. The effect of physical quantities on the temperature profiles is discussed in detail.